2007
DOI: 10.1194/jlr.m600343-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Effects of forced uncoupling protein 1 expression in 3T3-L1 cells on mitochondrial function and lipid metabolism

Abstract: Obesity-related increase in body fat mass is a risk factor for many diseases, including type 2 diabetes. Controlling adiposity by targeted modulation of adipocyte enzymes could offer an attractive alternative to current dietary approaches. Brown adipose tissue, which is present in rodents but not in adult humans, expresses the mitochondrial uncoupling protein 1 (UCP1) that promotes cellular energy dissipation as heat. Here, we report on the direct metabolic effects of forced UCP1 expression in white adipocytes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
51
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(61 citation statements)
references
References 60 publications
10
51
0
Order By: Relevance
“…Our results are also in total agreement with results recently obtained by Si et al (Si et al, 2007) using 3T3-L1 cells that ectopically expressed UCP1. These authors show that oxygen consumption and FFA β-oxidation were minimally affected by mitochondrial uncoupling triggered by UCP-1 overexpression.…”
Section: Discussionsupporting
confidence: 83%
“…Our results are also in total agreement with results recently obtained by Si et al (Si et al, 2007) using 3T3-L1 cells that ectopically expressed UCP1. These authors show that oxygen consumption and FFA β-oxidation were minimally affected by mitochondrial uncoupling triggered by UCP-1 overexpression.…”
Section: Discussionsupporting
confidence: 83%
“…In other words, uncoupling increases cellular metabolic demand since uncoupling OXPHOS lowers ATP production and increases the demand for reducing equivalents to restore/maintain mitochondrial membrane potential, thereby increasing substrate catabolism, which would theoretically decrease triglyceride (TG) stores in adipocytes. Indeed, although mitochondrial dysfunction could represent a major cause of lipid metabolism disorders and pathological triglyceride accumulation in several cell lines (50, 75), we and others have shown that mitochondrial uncoupling in adipocytes triggers lipolysis, limits fatty acid synthesis, and leads to a reduction in TG content (40,61,65,67,73), a characteristic also found during the "dedifferentiation" of adipocytes (86).Mature adipocyte dedifferentiation has been defined as the acquisition of a more primitive phenotype and gain of cell proliferative ability (48) as well as a reduction in TG content in adipocytes (29,52). In this study, we will refer to adipocyte dedifferentiation as a reduction of TG content and downregulation of adipogenic markers and effectors.…”
mentioning
confidence: 99%
“…Indeed, expression of uncoupling protein-1 (UCP1) in white and brown adipose cells of aP2-Ucp1 mice has been reported to lower body weight, to change fat distribution in the body (enlarged gonadal fat and decreased subcutaneous fat), and to prevent development of genetic or dietary obesity (38,39,41). Mitochondrial uncoupling induced by pharmacological molecules such as FCCP or ectopic UCP1 expression also leads to 3T3-L1 adipocyte dedifferentiation controlled by modifications in the expression of many genes (65,67,73).…”
mentioning
confidence: 99%
“…This suggests that a high level of the Grb10 gene could affect insulin resistance in the Meg1 Tg mouse. The reduction in intracellular lipid by constitutive expression of Ucp1 reflects down-regulation of fat synthesis rather than up-regulation of fatty acid oxidation [32]. The down-regulation of Ucp1 in Meg1Tg mice fed HFD could explain the non-obese character of the Meg1 Tg mouse.…”
Section: Discussionmentioning
confidence: 99%